2020
DOI: 10.1093/braincomms/fcaa170
|View full text |Cite
|
Sign up to set email alerts
|

Current knowledge of SLC6A1-related neurodevelopmental disorders

Abstract: Advances in gene discovery have identified genetic variants in the solute carrier family 6 member 1 (SLC6A1) gene as a monogenic cause of neurodevelopmental disorders, including epilepsy with myoclonic atonic seizures, autism spectrum disorder, and intellectual disability. The SLC6A1 gene encodes for the GABA transporter protein type 1 (GAT1), which is responsible for the reuptake of the neurotransmitter GABA, the primary inhibitory neurotransmitter in the central nervous system, from the extracellular space. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(105 citation statements)
references
References 47 publications
4
101
0
Order By: Relevance
“…Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that genes include SPHK2 [ 82 ], NPC1L1 [ 83 ], CNTFR (ciliaryneurotrophic factor receptor) [ 84 ], SLC2A4 [ 85 ], EDA (ectodysplasin A) [ 86 ], TGM2 [ 87 ], GCK (glucokinase) [ 88 ], FASN (fatty acid synthase) [ 89 ], FAP (fibroblast activation protein alpha) [ 90 ], PRNP (prion protein) [ 91 ], LYVE1 [ 92 ], SERPINE1 [ 93 ], TNF (tumor necrosis factor) [ 94 ], FASLG (Fas ligand) [ 95 ...…”
Section: Discussionmentioning
confidence: 99%
“…Genes such as KCNE5 [ 45 ], SHANK3 [ 46 ], CASQ2 [ 47 ], EDNRA (endothelin receptor type A) [ 48 ], EPHB4 [ 49 ], ALPK3 [ 50 ], WNT11 [ 51 ], IRAK2 [ 52 ], FBN1 [ 53 ], SFRP2 [ 54 ], CLCA2 [ 55 ], NEXN (nexilin F-actin binding protein) [ 56 ], PALLD (palladin, cytoskeletal associated protein) [ 57 ], DAB2 [ 58 ], NRP2 [ 59 ], THBS2 [ 60 ], CSF1R [ 61 ], KCNA2 [ 62 ], CACNA1C [ 63 ], F2R [ 64 ], UCHL1 [ 65 ], CCL18 [ 66 ], ITGB1BP2 [ 67 ] and FMOD (fibromodulin) [ 68 ] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [ 69 ], Liu et al [ 70 ], Eltokhi et al [ 71 ], Cai et al [ 72 ], Pfeiffer et al [ 73 ], Lin et al [ 74 ], Royer-Zemmour et al [ 75 ], Pastor et al [ 76 ], Goodspeed et al [ 77 ], Zhang et al [ 78 ], Rogers et al [ 79 ], Su et al [ 80 ] and Foale et al [ 81 ] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were the genes expressed in progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that genes include SPHK2 [ 82 ], NPC1L1 [ 83 ], CNTFR (ciliaryneurotrophic factor receptor) [ 84 ], SLC2A4 [ 85 ], EDA (ectodysplasin A) [ 86 ], TGM2 [ 87 ], GCK (glucokinase) [ 88 ], FASN (fatty acid synthase) [ 89 ], FAP (fibroblast activation protein alpha) [ 90 ], PRNP (prion protein) [ 91 ], LYVE1 [ 92 ], SERPINE1 [ 93 ], TNF (tumor necrosis factor) [ 94 ], FASLG (Fas ligand) [ 95 ...…”
Section: Discussionmentioning
confidence: 99%
“…KCNE5 [45], SHANK3 [46], CASQ2 [47], EDNRA (endothelin receptor type A) [48], EPHB4 [49], ALPK3 [50], WNT11 [51], IRAK2 [52], FBN1 [53], SFRP2 [54], CLCA2 [55], NEXN (nexilin F-actin binding protein) [56], PALLD (palladin, cytoskeletal associated protein) [57], DAB2 [58], NRP2 [59], THBS2 [60], CSF1R [61], KCNA2 [62], CACNA1C [63], F2R [64], UCHL1 [65], CCL18 [66], ITGB1BP2 [67] and FMOD ( bromodulin) [68] were reportedly involved in cardio vascular diseases, but these genes might be key for progression of obesity associated type 2 diabetes mellitus. Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that SPHK2 [82], NPC1L1 [83], CNTFR (ciliaryneurotrophic factor receptor)…”
Section: Discussionmentioning
confidence: 99%
“…The prominent epilepsy syndrome was epilepsy with myoclonic-atonic seizure (24%), and many patients also had absence or atypical absence seizure (72%). On EEG, many patients have generalized epileptiform discharges, notably in the frequency of 3 Hz, as well as generalized background slowing [118, 119].…”
Section: Slc6a1-related Disordermentioning
confidence: 99%
“…It was first described in 2015 among a cohort of patients with Doose syndrome [116], but the phenotype continues to expand as more patients are identified [117]. A recent compilation of 116 patients with SRD identified the core features of the disorder to include epilepsy (91%), developmental delay or cognitive impairment (82%), and autistic traits (23%) [118]. The prominent epilepsy syndrome was epilepsy with myoclonic-atonic seizure (24%), and many patients also had absence or atypical absence seizure (72%).…”
Section: Slc6a1-related Disordermentioning
confidence: 99%